Aplicación móvil para manejo de la información y divulgación del proceso de refugio en Costa Rica: caso desarrollo de appAyuda (ACNUR CR) - Schmidt-Peralta, Jeff (2019)
UNHCR is a United Nations Refugee Agency, a non-profit organization dedicated to help and protect people displaced around the world. In this context, this paper present details of the development of a mobile application (app), which objective is provide an information platform about UNHCR (ACNUR) in Costa Rica. This paper includes references of similar apps, information requirements, architecture design, user interface and other aspects of the app.